Hydrographic And Hydrochemical Characteristics of the Landslide Lake Jazerske (Spišska Magura, Northern Slovakia) - Molenda Tadeusz (Limnological Review, 2018)
This article presents the hydrographic and hydrochemical characteristics of this lake. Lake Jazerske is located in the Western Carpathians (Spiš Magura) in northern Slovakia. It occupies a depression that was formed at the foot of the main scarp of a landslide. Below the lake, there are small intercolluvial depressions that have been transformed into wetlands (peat bogs). The studied lake is very small. Its area is 3600 m2 and its length is 85 m. The maximum depth of the lake is 7.2 m and its capacity is 17 000 m3. The lake is supplied by an inflow of groundwater via fractured aquifers. During periods of heavy rainfall and snow melting, the lake is also supplied by the water from surface runoff. On the main slope of the landslides, traces of ephemeral courses were also found. During the periods of increased supply (spring snow melting, summer rainfall), the outflow of water from the lake occurs both on the surface and underground. In terms of its hydrochemistry, the lake water represents the four-ion type - bicarbonate-sulphate-calcium-magnesium. The concentrations of various ions is characteristic of the shallow groundwater of the Carpathian flysch. The predominant cation, the average concentration of which is 52 mg dm-3, is calcium. The dominant anion is carbohydrates with an average concentration of 163 mg dm-3. What is interesting is the very low levels of chlorides, which do not exceed 2 mg dm-3. The electrolytic conductivity of the water flowing out of the lake ranged from 290 to 328 μS cm-1.